A Novel Synthetic Route to 3,5-Diaryl-N-Formyl-2-Pyrazoline - Al-Issa, S.A.; Ghulikah, H.A. (Asian Journal of Chemistry, 2010)
Some new 3,5-diaryl-N-formyl-2-pyrazoline derivatives (IIIa-c) have been prepared. Treatment of (IIIa-c) with hydrazine hydrate yielded N-formyl hydrazone derivatives (IVa-c), N-formyl aryl hydrazone derivatives (Va-d) were prepared by condensing compound (IIIa-c) with aromatic amine, treatment of (IIIa-c) with isonicotinic hydrazide in ethyl alcohol afforded N-formyl-1-isonicotinic hydrazone derivatives (VIa-c), N-substituted-thiazolidin- 4-one-derivatives (VIIa-f) was prepared. Compounds (IIIa-c) condensed with hydroxylamine to give the corresponding oxime derivatives (VIIIa-c).